Fraud Prevention through Risk Management and Good Governance: The Ethics of Organizational Behavior Moderation: English - Nadila Noor Azizah; Irwansyah Irwansyah (Owner : Riset dan Jurnal Akuntansi, 2026)
This research aims to analyze the influence of risk management and good governance on fraud prevention with the ethics of organizational behaviour as a moderating variable. This type of research is quantitative, and data collection was carried out through a questionnaire. The research was conducted at the Inspectorate of East Kalimantan Province with a sample of 42 auditors. The data analysis technique used is Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1 software. The results showed that risk management and good governance have a positive and significant effect on fraud prevention. The ethics of organizational behavior is able to moderate the influence of risk management on fraud prevention, but the ethics of organizational behavior is not able to moderate the effect of good governance on fraud prevention.